MAXIMIZING OPERATIONAL EFFICIENCY THROUGH INTEGRATED SUPPLY CHAIN MANAGEMENT - Zulfatun Anisah (PAPUA: International Journal of Sharia Business Management, 2024)
The study addresses the critical issue of optimizing supply chain management (SCM) for operational efficiency in a highly competitive and dynamic global market. The primary problem investigated is how companies can enhance their SCM processes to achieve significant operational improvements through various strategies, technologies, and practices. This research employs a comprehensive methodology, incorporating qualitative and quantitative analyses to examine key aspects such as inventory management, supplier relationships, technological integration, risk management, sustainability practices, and cross-departmental collaboration. The research methodology involves an in-depth analysis of SCM practices across multiple industries, utilizing case studies, surveys, and interviews with supply chain professionals. This mixed-methods approach provides a holistic understanding of how different elements of SCM contribute to overall operational efficiency. The findings reveal that effective inventory management, particularly through Just-In-Time (JIT) practices and Economic Order Quantity (EOQ), significantly reduces holding costs and minimizes waste. Strong supplier relationships are identified as pivotal for ensuring a reliable supply of quality materials, enhancing coordination, pricing, and delivery schedules. Technological integration, including Enterprise Resource Planning (ERP) systems, Internet of Things (IoT), and big data analytics, plays a crucial role in optimizing SCM by improving decision-making and operational visibility. Effective risk management strategies, including supplier diversification and proactive risk assessment, are essential for maintaining supply chain resilience. Sustainability practices contribute to operational efficiency and corporate social responsibility, meeting regulatory requirements and consumer expectations. Cross-departmental collaboration ensures seamless information flow and coordinated efforts, leading to improved Supply Chain Performance.